2022
DOI: 10.1186/s12870-022-03818-z
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of leaf functional traits under climatic warming in an arid ecosystem

Abstract: Background Climatic warming is increasing regionally and globally, and results concerning warming and its consequent drought impacts have been reported extensively. However, due to a lack of quantitative analysis of warming severities, it is still unclear how warming and warming-induced drought influence leaf functional traits, particularly how the traits coordinate with each other to cope with climatic change. To address these uncertainties, we performed a field experiment with ambient, modera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 87 publications
0
6
0
Order By: Relevance
“…The dynamics in the relationships are in agreement with the previous study by Pollastrini et al (2016), who reported the changing ChlF‐trait relationships across species and sites. In addition, Yu et al (2022) also found that warming changed the relationships between ChlF parameters and specific leaf area, with significance under control and moderate warming and non‐significance under severe warming. This study revealed the relationship between fluorescence and leaf traits and the changes in this relationship with light conditions, unravelling the complex dynamics of plant photosynthesis and stress responses.…”
Section: Discussionmentioning
confidence: 99%
“…The dynamics in the relationships are in agreement with the previous study by Pollastrini et al (2016), who reported the changing ChlF‐trait relationships across species and sites. In addition, Yu et al (2022) also found that warming changed the relationships between ChlF parameters and specific leaf area, with significance under control and moderate warming and non‐significance under severe warming. This study revealed the relationship between fluorescence and leaf traits and the changes in this relationship with light conditions, unravelling the complex dynamics of plant photosynthesis and stress responses.…”
Section: Discussionmentioning
confidence: 99%
“…Based on PCA analysis, we found that these photosynthetic traits were convergent more in north-cold boreal forest than in high-cold alpine forest. It implies that the former would exert a joint response to local environmental change [ 88 ]. Additionally, the results from SEM were partially inconsistent with those using linear regressions in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The reference CO 2 concentration in the leaf chamber was kept at 360–400 µmol CO 2 mol − 1 , with a relative air humidity of 50-70%, and saturating photosynthetic photon flux density was set at 1500 µmol·m − 2 ·s − 1 . The fully expanded youngest leaves per plant per species in each plot were placed into the cuvette, and at least three measurements were made for each species in each plot [ 88 ]. The maximum net photosynthetic rate per unit area ( A area ) was directly obtained, and the maximum net photosynthetic rate per unit mass ( A mass ) was then calculated by the equation:…”
Section: Discussionmentioning
confidence: 99%
“…Since the adjustment of leaf economic traits is deeply correlated with photosynthesis and productivity, it is necessary to quantitatively analyze the processes of leaf economic traits driven by environmental and intrinsic factors ( Li et al., 2021a ). The structural equation model has been used to quantitatively analyze the causal relationship between variables, which has been more mature in the field of plant functional trait research ( Vile et al., 2006 ; Yu et al., 2022 ). This study hypothesized that elevation drives changes in leaf morphological characteristics and nutrient content that affect photosynthesis ( Figure 2 ) as an initial model.…”
Section: Discussionmentioning
confidence: 99%